Riders to Moon Rock - Fenady, Andrew J. (Waterville, Me. : Thorndike Press, 2005)
Like the stony peak of Moon Rock, Shannon knew what it was to be beaten by the elements yet stand tall and proud despite numerous storms. Shannon never quite fit in with the rest of the world. First raised by Kiowas and then taken in by a wealthy rancher, he found himself rejected by society time after time. But now Shannon was determined to wait out his enemies and take what was rightfully his - no matter what the cost.
86739
Keywords: Ranching -- Fiction; Large type books; Texas -- Fiction; Western stories